Corporate Governance Mechanism and Capital Structure Decision: Evidence from Indonesia - Lestari, Agnes; Murhadi, Werner R.; Ernawati, Endang (Journal of Entrepreneurship and Business, 2024)
Purpose: Decisions related to the capital structure are crucial for companies because the proportion of funding from debt and equity determines the company's value and is directly related to shareholders' welfare. This study aims to examine how corporate governance affects the capital structure. Method: Board size, board independence, ownership concentration, audit reputation, management ownership, and institutional ownership are the independent variables considered in this study. In contrast, control variables were defined as firm size, liquidity, profitability, and growth. In order to determine how corporate governance affects capital structure in a sample of 395 non-financial companies listed on the Indonesia Stock Exchange, this study employs multiple linear regression analysis. Result: The capital structure is significantly impacted negatively by board size, ownership concentration, firm size, profitability, and growth while positively impacted by independent commissioners, auditor reputation, managerial ownership, and institutional ownership. Liquidity has no impact on the capital structure.